1998
DOI: 10.1002/(sici)1097-0290(19981105)60:3<391::aid-bit17>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Batch phenol degradation byCandida tropicalis and its fusant

Abstract: Phenol degradation by Candida tropicalis and its fusant, which is produced using protoplast fusion as a selective technique, is evaluated under batch and high concentration conditions. The respirometric data show that oxygen uptake activities of both yeast strains peak at pH 7.0 and 32°C, but the fusant is more active than the control strain. Although the data show that both yeast strains are capable of sustaining discernible degradation in the presence of phenol inhibition, however, the C. tropicalis fusant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Only few workers have presented works on phenol degradation of concentrations lower than 250 mg/L (Hill and Robinson, 1975;Lakhwala et al, 1992;Mordocco et al, 1999;Oboirien et al, 2005). Microbial degradation of phenol has been actively studied and these studies have shown that phenol can be aerobically degraded by wide variety of fungi and bacteria cultures such as Candida tropicalis (Chang et al, 1998;Ruiz-ordaz et al, 1998;2001) Acinetobacter calcoaceticus (Paller et al, 1995) Alcaligenes eutrophus (Hughes et al, 1984;Leonard and Lindley, 1998) Pseudomonas putida (Hill and Robinson, 1975;Kotturi et al, 1991;Nikakhtari and Hill, 2006) and Burkholderia cepacia G4 (Folsom et al, 1990;Solomon et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Only few workers have presented works on phenol degradation of concentrations lower than 250 mg/L (Hill and Robinson, 1975;Lakhwala et al, 1992;Mordocco et al, 1999;Oboirien et al, 2005). Microbial degradation of phenol has been actively studied and these studies have shown that phenol can be aerobically degraded by wide variety of fungi and bacteria cultures such as Candida tropicalis (Chang et al, 1998;Ruiz-ordaz et al, 1998;2001) Acinetobacter calcoaceticus (Paller et al, 1995) Alcaligenes eutrophus (Hughes et al, 1984;Leonard and Lindley, 1998) Pseudomonas putida (Hill and Robinson, 1975;Kotturi et al, 1991;Nikakhtari and Hill, 2006) and Burkholderia cepacia G4 (Folsom et al, 1990;Solomon et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is an organic, aromatic compound that occurs naturally in the environment (Prpich and Daugulis, 2005), but is more commonly produced artificially from industrial activities such as petroleum processing, plastic manufacturing, resin production, pesticide production, steel manufacturing and the production of paints and varnish (Mahadevaswamy et al, 1997;Bandyopadhyay et al, 1998). This aromatic compound is water-soluble and highly mobile (Collins and Daugulis, 1997) and as such waste waters generated from these industrial activities contain high concentrations of phenolic compounds (Chang et al, 1998) which eventually may reach down to streams, rivers, lakes, and soil, which represent a serious ecological problem due to their widespread use and occurrence throughout the environment (Fava et al, 1995). Phenol is a listed priority pollutant by the U.S. Environmental Protection Agency (EPA, 1979) and is considered to be a toxic compound by the Agency for Toxic substances and Disease Registry (ATSDR, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques involving physical, chemical and biological methods have been used for the removal of phenol from industrial effluents and contaminated The meta-cleavage pathway for the biodegradation of phenol A= Phenol, B= Catechol, C= 2-Hydroxymuconic semialdehyde, D= 2-Hydroxymuconate, E= 2-Oxo-4-enoadipate, F= 2-Oxo-penta-4-enoate, G= Pyruvate, H= Acetaldehyde, I= Acetyl Co A, E1= Monooxygenase phenol hydroxylase, E2=Catechol-2, 3-dioxygenase, E3= Hydrolase, E4= Dehydrogenase, E5= Isomerase, E6= Decarboxylase, E7= Hydrotase, E8= Aldolase waters with bioremediation receiving the most attention due to its environmental friendliness, its, ability to completely mineralize toxic organic compounds and of low-cost (Kobayashi and Rittman, 1982;Prpich and Daugulis, 2005). Microbial degradation of phenol with different initial concentrations ranging from 50-2000 mg/L have been actively studied using shake flask, fluidized-bed reactor, continuous stirred tank bioreactor, multistage bubble column reactor, air-lift fermenter and two phase partitioning bioreactor methods (Bettmann and Rehm, 1984;Sokol, 1988;Annadurai et al, 2000;Reardon et al, 2000;Ruiz-ordaz et al, 2001;Oboirien et al, 2005;Prpich and Daugulis, 2005;Saravanan et al, 2008) and these studies have shown that phenol can be aerobically degraded by wide variety of fungi and bacteria cultures such as Candida tropicalis (Ruiz-ordaz et al, 2001, Chang et al, 1998Ruiz-ordaz et al, 1998); Acinetobacter calcoaceticus (Paller et al, 1995); Alcaligenes eutrophus (Hughes et al, 1984;Leonard and Lindley, 1998); Pseudomonas putida (Hill and Robinson, 1975;Kotturi et al, 1991;Nikakhtari and Hill, 2006); and Burkholderia cepacia G4 (Folsom et al,1990, Solomon et al,1994. In microbial degradation of phenol under aerobic conditions, the degradation is initiated by oxygenation in which the aromatic ring is initially monohydroxylated by a mono oxygenase phenol hydroxylase at a position ortho to the pre-existing hydroxyl group to form catechol.…”
Section: Introductionmentioning
confidence: 99%
“…(Neujahr et al, 1974). Chang et al (1998) determined the optimum pH at 7 and the optimum temperature of 32°C for Candida tropicalis and its fusant. Data demonstrated a better phenol degradation received with the fusant and also lower sensitivity to phenol inhibition as compared to the control strain.…”
Section: Aparatus and Conditionsmentioning
confidence: 99%